2008
DOI: 10.1161/circep.108.784272
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Begets Atrial Fibrillation

Abstract: Background-The mechanism(s) for acute changes in electrophysiological properties of the atria during rapid pacing induced atrial fibrillation (AF) is not completely understood. We sought to evaluate the contribution of the intrinsic cardiac autonomic nervous system in acute atrial electrical remodeling and AF induced by 6-hour rapid atrial pacing. Methods and Results-Continuous rapid pacing (1200 bpm, 2ϫ threshold [TH]) was performed at the left atrial appendage. Group 1 (nϭ7) underwent 6-hour pacing immediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(76 citation statements)
references
References 30 publications
2
74
0
Order By: Relevance
“…495,496 Although AF can typically be reversed in its early stages, it becomes more difficult to eliminate over time due to such remodelling. 238,497 Dominant-frequency analysis points to an evolution of mechanisms in AF patients, with PV sources becoming less predominant as AF becomes more persistent and atrial remodelling progresses. 498 The data suggest that in patients with long-standing persistent AF, atrial remodelling augments the number of AF drivers and shifts their location away from the PV/ostial region.…”
Section: Impact Of Ongoing Atrial Fibrillation On Electrical and Strumentioning
confidence: 99%
“…495,496 Although AF can typically be reversed in its early stages, it becomes more difficult to eliminate over time due to such remodelling. 238,497 Dominant-frequency analysis points to an evolution of mechanisms in AF patients, with PV sources becoming less predominant as AF becomes more persistent and atrial remodelling progresses. 498 The data suggest that in patients with long-standing persistent AF, atrial remodelling augments the number of AF drivers and shifts their location away from the PV/ostial region.…”
Section: Impact Of Ongoing Atrial Fibrillation On Electrical and Strumentioning
confidence: 99%
“…RAP can shorten ERP and increase ERP dispersion and ΣWOV, which were all reversed after GP ablation. Implementing GP ablation or autonomic blockers (atropine or propranolol) followed by RAP can prevent induced spontaneous AF and atrial electrical remodeling 26, 27. In our study, administrating A‐803467 can effectively attenuate ERP shortening and suppress increased ERP dispersion and ΣWOV, indicating a pharmacological denervation effect by this selective Na v 1.8 blocker.…”
Section: Discussionmentioning
confidence: 52%
“…This could suggest that blocking Na v 1.8 could avoid functional substrate forming in PV myocardium, probably as a result of inhibiting GP function and atrial electrical remodeling. Although we could not deny the fact that sodium pentobarbital has been reported vagolytic and may increase the ERP value when applying,29, 30 the effect of A‐803467 on ERP in the present study is still established, since both groups were treated equally with the anesthetic to eliminate bias between groups, and the minimum dosage was used to reduce the possibility of unnecessary influence, as in our previously published studies 18, 26, 31, 32…”
Section: Discussionmentioning
confidence: 72%
“…Lu et al found that either GP ablation or autonomic blockade reduced ERP dispersion and prevented ERP shortening and AF inducibility in a canine model of 6‐hour RAP, suggesting the presence of autonomic remodeling and its importance in facilitating atrial electrical remodeling in the acute stage 7. Direct neural recordings from the GP also revealed that as AF continued, the activity of the major LA GP increased progressively, which helped maintain short and dispersed ERPs to sustain AF.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, autonomic remodeling plays an important role in the pathogenesis of AF. Several publications demonstrated that hyperactivity or imbalance of the cardiac autonomic nervous system (ANS) facilitates the initiation and maintenance of AF 4, 5, 6, 7, 8, 9, 10, 11. Hyperactivity of the cardiac ANS and AF also form a vicious cycle in which the former can initiate AF and the latter further enhance the activity of the cardiac ANS to perpetuate AF 7, 9…”
Section: Introductionmentioning
confidence: 99%